Enhancing use of the cubic space of hose export containers in an agro-industrial company in Perú (2021)
This article describes the current situation of the export of hydraulic hoses in Peru, analyzes the main factors that increase the export cost and proposes a linear programming model to determine the type of container to use according to the exposed variables.